2020
DOI: 10.1074/jbc.ra120.014018
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional repressor BCL11A promotes breast cancer metastasis

Abstract: The phenotypes of each breast cancer subtype are defined by their transcriptomes. However, the transcription factors that regulate differential patterns of gene expression that contribute to specific disease outcomes are not well understood. Herein, using gene silencing and overexpression approaches, RNA-Seq, and splicing analysis, we report that the transcription factor B-cell leukemia/lymphoma 11A (BCL11A), is highly expressed in triple-negative breast cancer (TNBC) and drives metastatic disease. Moreover, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 70 publications
(79 reference statements)
2
20
0
Order By: Relevance
“…In contrast, Bcl11a expression was elevated by an average of 2.1-fold ( p = 0.00001) in samples with SB insertions targeting this gene. This is consistent with the transforming effect of Bcl11a when overexpressed 42 . We next tested for a link between gCIS-expression and tumor histology.…”
Section: Resultssupporting
confidence: 88%
“…In contrast, Bcl11a expression was elevated by an average of 2.1-fold ( p = 0.00001) in samples with SB insertions targeting this gene. This is consistent with the transforming effect of Bcl11a when overexpressed 42 . We next tested for a link between gCIS-expression and tumor histology.…”
Section: Resultssupporting
confidence: 88%
“…Besides, by directly interacting with the 3'UTR of Bcl2, miR-190b induces osteosarcoma cell apoptosis and confers radio-sensitivity to gastric cancer cells (58,59). According to reports, BCL11A acts as a carcinogenic gene for a variety of human cancers, such as breast cancer (60) proliferation and migration ability in the pathogenesis of breast cancer (64).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, by directly interacting with the 3’UTR of Bcl2, miR-190b induces osteosarcoma cell apoptosis and confers radio-sensitivity to gastric cancer cells ( 58 , 59 ). According to reports, BCL11A acts as a carcinogenic gene for a variety of human cancers, such as breast cancer ( 60 ), laryngeal squamous cell carcinoma ( 61 ), high-risk neuroblastoma ( 62 ), non-small cell lung cancer ( 63 ) etc. In addition, the expression of PSMG3-AS1 in breast cancer tumor tissues and cell lines was increased, and PSMG3-AS1 as a sponge of miR-143-3p enhanced the proliferation and migration ability in the pathogenesis of breast cancer ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al [105] found that SMPD1 stimulates the drug resistance in colorectal cancer, but this gene might be linked with development of PDAC. Liu et al [106], Yang et al [107], Song et al [108], Seachrist et al [109], Zhu et al [110], Wu et al [111], Wang et al [112], Yi et al [113], Lan et al [114] and Appert-Collin et al [115] revealed that PADI4, MAOB (monoamine oxidase B), TRPC6, BCL11A, CXCR5, TCF7, POU2F2, SLC4A1, STK17B and LRP1 were associated with cancer cell invasion, but these genes might be liable for progression of PDAC. Kairouz et al [116], Diez-Bello et al [117], Xue et al [118], Abo-Elfadl et al [119], Li et al [120] and Zhao et al [121] reported that GRB14, TRPC6, ZFPM2, TNFRSF13B, ADAM19 and PIK3IP1enhance the cancer cell proliferation, but this gene might be involved in advancement of PDAC.…”
Section: Discussionmentioning
confidence: 99%